STRATEGI PEMASARAN ONLINE PADA PRODUK TABUNGAN EASY WADIAH TERHADAP MINAT NASABAH MELALUI BSI-MOBILE - Khotimah, Dwi Khusnul; Fasa, Muhammad Iqbal (Jurnal Ilmiah Ekonomi, Manajemen dan Syariah, 2024)
Increasingly developing technology makes it easier for banking institutions to take advantage of technological advances. Therefore, marketing management for Wadiah savings products is becoming increasingly sophisticated because of the digital era. However, digital-based sharia marketing activities have not been fully realized to their full potential as seen from the diagram which has experienced a decline. This researcher uses qualitative research on marketing management for product savings based on customer interest, which is expected to increase and develop marketing management through BSI- Mobile. Data collection was carried out through observation, interviews, and supported by other data such as journals, books and related theses using the analytical techniques used, namely reducing, presenting data and providing conclusions. The research results show that marketing management strategies promote by utilizing social media such as BSI web forms and BSI Mobile Banking. From the results of using this media, the number of customers who carry out wadiah savings activities easily via BSI-Mobile has increased